1999
DOI: 10.1046/j.1464-5491.1999.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones: a new class of antidiabetic drugs

Abstract: Thiazolidinediones (TZDs) are a new class of oral antidiabetic agents. They selectively enhance or partially mimic certain actions of insulin, causing a slowly generated antihyperglycaemic effect in Type 2 (noninsulin dependent) diabetic patients. This is often accompanied by a reduction in circulating concentrations of insulin, triglycerides and nonesterified fatty acids. TZDs act additively with other types of oral antidiabetic agents (suphonylureas, metformin and acarbose) and reduce the insulin dosage requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
308
1
12

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(336 citation statements)
references
References 136 publications
12
308
1
12
Order By: Relevance
“…Increased insulin sensitivity was evident in terms of both the insulin sensitivity index ( S I ), which reflects the actions of insulin to stimulate peripheral glucose uptake and suppress hepatic glucose production, and its counterpart ( S IN ) in the model of NEFA kinetics, which describes the potency of insulin to promote fatty acid uptake and inhibit peripheral lipolysis. The dual improvement in these indices in the obese cats is consistent with the fact that pioglitazone amplifies insulin signaling in multiple organs, including the muscle, adipose tissue, and liver, in other species 5, 7, 17, 18. In addition, it is encouraging with respect to the therapeutic potential of pioglitazone in diabetic cats, and perhaps in cats with hepatic lipidosis.…”
Section: Discussionsupporting
confidence: 70%
“…Increased insulin sensitivity was evident in terms of both the insulin sensitivity index ( S I ), which reflects the actions of insulin to stimulate peripheral glucose uptake and suppress hepatic glucose production, and its counterpart ( S IN ) in the model of NEFA kinetics, which describes the potency of insulin to promote fatty acid uptake and inhibit peripheral lipolysis. The dual improvement in these indices in the obese cats is consistent with the fact that pioglitazone amplifies insulin signaling in multiple organs, including the muscle, adipose tissue, and liver, in other species 5, 7, 17, 18. In addition, it is encouraging with respect to the therapeutic potential of pioglitazone in diabetic cats, and perhaps in cats with hepatic lipidosis.…”
Section: Discussionsupporting
confidence: 70%
“…Steppan et al isolated resistin as the product of a gene whose expression is suppressed in response to rosiglitazone, a peroxisome proliferator-activated receptor-g (PPARg) agonist that enhances insulin sensitivity in type 2 diabetic patients. [53][54][55][56] Kim and et al 57 identified resistin as the adipose secretory factor or ADSF, by microarray analyses. A third group initially found resistin, which they named 'FIZZ3', as an expressed sequence tag related to a protein they found to be induced during lung inflammation known as 'found in inflammatory zone 1'.…”
Section: Resistinmentioning
confidence: 99%
“…This activation results in changes in the expression of numerous genes that are critically involved in glucose and lipid metabolism, as well as in insulin signal transduction. (76)(77)(78) Metformin, a biguanide antihyperglycemic agent that increases insulin sensitivity, has been shown to improve ovarian function and glucose metabolism in women with PCOS. (64,79) Metformin therapy not only decreases hyperandrogenism and insulin resistance but also improves ovulation rates, cervical scores, and pregnancy rates in clomiphene citrate-resistant women with PCOS.…”
Section: Treatment With Insulin-sensitizing Agents In Pcosmentioning
confidence: 99%
“…This is often accompanied by a reduction in circulating concentrations of insulin, triglycerides and nonesterified fatty acids. (76) Troglitazone, one of the insulin-sensitizing compounds, thiazolidinediones, is a ligand for peroxisome proliferator-activated receptor-gamma (PPAR-γ) and is effective in the treatment of both noninsulin-dependent diabetes mellitus (NIDDM) as well as PCOS. (77) Administration of troglitazone to women with PCOS and impaired glucose tolerance ameliorates the metabolic and hormonal derangements, resulting in improvement of insulin sensitivity and hyperandrogenism as well as restoration of ovulation.…”
Section: Treatment With Insulin-sensitizing Agents In Pcosmentioning
confidence: 99%